Offensive and defensive efficacy among male and female elite foil fencers - Kontochristopoulos, N.; Tsolakis, C. (Journal of Human Sport & Exercise, 2020)
Fencing is a combat sport, where beyond physical and physiological demands, strategy and tactics are crucial factors in order to identify fencers` performance. Fencers` tactical movements can be separated in preparatory actions and final actual offensive (attacks) and defensive (parries and counterattacks) actions. The aim of this study is to analyse the tactical choices of elite male and female qualifiers foil fencers in finals and semi-finals bouts of the 2016-17 FIE (International Fencing Federation) competitions. Attacking and defending points were recorded, compared with the type of point, the section thrusts were landed and the time period they were noted. The present study revealed significant difference between offensive and defensive efficacy in both male (p < .003) and female fencers (p = .019). Male fencers showed greater activation than women (p = .003), finishing their bouts much earlier (p = .000), since they needed less time to accomplish an actual action (p = .001). In conclusion, male could be characterized as ``permanently pressing`` fencers, while female adopted a ``manoeuvring-attacking`` style, since male fencers had greater percentage of total actions on the middle section of the piste (p = .011) and female fencers had greater number of defending actions on the back section (p = .033), respectively.